Предметно-об'єктна сфера інституту контролю - Хмельков, Андрій Володимирович (My University, 2017)
У статті, в межах формування системного уявлення про контрольну функцію фінансів та її реалізацію в економіці, розглянуто ланцюг понять: «інститут контролю» - «агент інституту контролю» - «предметно-об’єктна сфера інституту контролю», виходячи з неформального та формального змісту. У основному фокусі дослідження – предметно-об’єктна сфера контролю. Сформульовано авторське бачення предмета та об’єкта інституту контролю, розкрито їх структура, склад, а також взаємозв’язок між ними. Доведено еквівалентність понять «інститут контролю» та «державний фінансовий контроль». Акцентовано, що для предметної сфери державного фінансового контролю застосовується лише публічні ресурси, дії тощо. Розкриття поняття «інститут контролю» методами інституційного аналізу дало змогу здійснити сходження від абстрактного до конкретного досліджуваного ланцюга.
SUBJECT AND OBJECT SCOPE OF THE INSTITUTE OF CONTROL
This article considers the chain of the notions: “institution control” - “agent of the Institute of Control” - “subject and object scope of the institute of control”, based on informal and formal content in terms of forming a system concept of the control function of finance and its implementation in the economy. In the main focus of this research there is a subject and object scope of control. There has been stated the author’s vision of the subject and object of the control institute, their structure, composition, and the relationship between them have been determined. We prove the equivalence of the notions “institute of control” and “state financial control”. It has been pointed out that only public resources, actions, etc. are used in the subject scope of the state financial control. The essential features of the notion “institute of control” having been determined by means of institutional analysis made it possible to step down from the abstract to the concrete chain of interrelated notions. The mechanism of the formation of the institute of control as a social norm has been studied at both informal and informal levels. At the informal level there is restrictive framework created to prevent treating public funds as personal. At the formal level, the Institute of control acquires established patterns in the form of the state financial control and its systems. There has been demonstrated that filling institute of control and its agents with the formal content is carried through administrative or legislative actions of the state.
Keywords: Research Subject Categories::SOCIAL SCIENCES; інститут контролю; агент інституту контролю; предмет інституту контролю; об’єкт інституту контролю; квазісуб’єкт державного фінансового контролю; принцип каузальності; система державного фінансового контролю; публічні фінанси; інституційна інфраструктура